2018
DOI: 10.28982/josam.443209
|View full text |Cite
|
Sign up to set email alerts
|

Which one is the first choice for rapid ventricular rate atrial fibrillation in emergency department: Metoprolol or Diltiazem? A randomized clinical trial

Abstract: Aim: Atrial fibrillation (AF) is the most common cardiac arrhythmia managed by emergency physicians. Primary goals of treatment are hemodynamic stabilization, ventricular rate control, and prevention of embolic complications. The aim of this study is to compare the drug responses of the patients who presented to the ED with AF with rapid ventricular response (AFRVR), their need for the second dosage and echocardiographic parameters. Methods: This is a prospective, single blind, randomized study. AFRVR patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…Demircan et al (13), showed that diltiazem and metoprolol were similar in efficacy and side effects in patients, regardless of EF; diltiazem also decreased the heart rate more quickly than metoprolol, and the reduction was greater at different time intervals. In support of this study, Memiş et al (14), showed that diltiazem was more effective in RVR and the EF value was the determining factor for maintaining rate control. Martindale et al (15), showed that diltiazem provides more effective rate control than metoprolol.…”
Section: Discussionsupporting
confidence: 69%
“…Demircan et al (13), showed that diltiazem and metoprolol were similar in efficacy and side effects in patients, regardless of EF; diltiazem also decreased the heart rate more quickly than metoprolol, and the reduction was greater at different time intervals. In support of this study, Memiş et al (14), showed that diltiazem was more effective in RVR and the EF value was the determining factor for maintaining rate control. Martindale et al (15), showed that diltiazem provides more effective rate control than metoprolol.…”
Section: Discussionsupporting
confidence: 69%
“…2 ). 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 These studies enrolled 1732 patients in emergency departments (thirteen studies) and intensive care unit settings (one study). These fourteen studies were pooled, as they each reported achievement of rate control target with diltiazem (n = 773) compared to metoprolol (n = 959) in patients with atrial fibrillation with rapid ventricular rate.…”
Section: Resultsmentioning
confidence: 99%